Tax planning and financial performance of insurance companies in Ghana: the moderating role of corporate governance - George Tackie; Samuel Kwaku Agyei; Isaac Bawuah; Vincent Adela; Ahmed Bossman (Cogent Business & Management, 2022)
The insurance industry is a contributor to gross domestic product (GDP) in the Ghanaian economy and, thus, effort at improving its financial soundness through tax planning (TP) could enhance its level of GDP contribution. Previous studies on TP have been conducted mainly among the non-financial firms, with few on banks. This study turns the attention of TP towards the insurance industry, which has been a good source of fund mobilization in the country. Within the systems panel dynamic generalized method of moments (GMM) framework, the study examined the moderating impact of corporate governance (CG) on the relationship between TP and the performance of insurance companies in Ghana. The study employs the causal design to examine the extent and nature of the cause-and-effect relationship between the quantitative variables used. The data comprised of 117 observations from 35 Ghanaian Insurance firms over the 2012-2017 period. The study found evidence of a non-linear relationship between tax planning measured by effective tax rate (ETR) and the performance of insurance companies measured by return on equity (ROE) and return on asset (ROA). Moreover, the study found that CG moderated the relationship between TP and the performance of insurance companies. The study recommends that managers of insurance companies intensify the CG measures to help mitigate the agency conflict and associated costs between management and shareholders.
Keywords: 650; corporate governance; return on equity; Effective tax rate; return on asset; tax planning